SIXTH GRADE STUDENTS' MISCONCEPTIONS ON DECIMAL NUMBERS THROUGH ROUTINE EXERCISE QUESTIONS - Lutfi Abdurahman; Tatang Herman (Jurnal Cakrawala Pendas, 2024)
Mathematics is an important subject in elementary school because it is the basis for understanding more complex mathematical concepts in the future. One of them is that students need to study number material in basic mathematical concepts because it is very important to master and understand, for example it can be used in commerce, measurement and technology. However, in the field, elementary school students are still found to have misconceptions about understanding the concept of comparing, ordering or calculating decimal numbers. This research uses a qualitative approach with a case study method. The subjects of this research were 4 class VI students at an elementary school in Banyuresmi sub-district, Garut. Data was collected through observation, interviews, and providing routine practice question sheets. The findings in this research are, 1) Some students have difficulty understanding decimal numbers and ordering them as well as performing addition calculation operations, 2) Some students consider decimal numbers with more digits after the comma as larger numbers, 3) There are also students who make mistakes. Storing numbers after commas can cause errors in calculations. So the alternative solution that can be given is that teachers can identify the source of student misconceptions by providing diagnostic tests, using more interactive learning methods, providing case examples from everyday life, providing more and varied exercises, providing continuous feedback. and be constructive towards student answers, and facilitate discussions that focus on problem solving. This will help students understand the concept of decimal numbers more effectively and efficiently.